A LabVIEW Based Optimization and Integration of Supersonic Wind Tunnel Instrumentation System - Jefri Abner Hamonangan; Prawito Prajitno; Agus Aribowo (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Indonesian National Institute of Aeronautics and Space have a supersonic wind tunnel for research in high speed object . The condition of LAPAN's supersonic wind tunnel can only be used for shockwave observation by using schlieren apparatus. The data acquisition system can not collect data from sting balance, some of the control panels are either not operational or it need calibration. Based from these conditions, this research is done to develop a new integrated control system and data acquisition so that the effectiveness of operation in terms of time and better data quality can be achieved. For angle of attack (AoA) control from manual operation, have been optimized to a digital control using PID control method. With the new system, the AoA control has been automated and a new testing option for moving the AoA while the wind tunnel running can be done. In terms of data acquisition, after the optimization it can collect better data, (noise / interference becomes smaller), and now it can record data from the balance, the pressure data, AoA position and block position can be recorded. The system was created using PXIe from National Instrument and LabVIEW graphical programming as user interface.